(untitled) (Physical Education, Health and Social Sciences, 2025)
The rapid advancement of Artificial Intelligence (AI) has the potential to transform teaching, learning, and school leadership practices. However, unequal access to digital infrastructure and persistent socioeconomic inequalities continue to limit the effective adoption of AI, particularly in public secondary schools in District Mardan, Khyber Pakhtunkhwa, Pakistan. This qualitative study explores how infrastructure gaps and inequality shape AI adoption from the perspectives of teachers and school heads. Data were collected through semi-structured interviews with five public secondary school teachers and five school heads. Thematic analysis revealed key barriers, including inadequate digital infrastructure, limited digital and AI-related skills, and socioeconomic disparities among students, lack of institutional support, and the absence of clear AI-related policies. Findings indicate that without addressing foundational infrastructure and equity issues, AI initiatives risk reinforcing existing educational inequalities. The study highlights the need for context-responsive policies, targeted professional development, and equitable investment in digital infrastructure to ensure inclusive and sustainable AI adoption in public secondary education.